2000
DOI: 10.1302/0301-620x.82b8.0821103
|View full text |Cite
|
Sign up to set email alerts
|

Limited dorsiflexion predisposes to injuries of the ankle in children

Abstract: Injuries to the ankle are common in children. We investigated whether decreased dorsiflexion predisposes to such fractures and sprains. Passive dorsiflexion in children with ankle injuries was compared with that in a control group of patients with a normal ankle. The uninjured side was examined to determine flexibility in those patients with ankle injuries. In 82, the mean dorsiflexion was 5.7° with the knee extended and 11.2° with the knee flexed. In 85 controls, the mean dorsiflexion was 12.8° with the knee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…Further, Tabrizi et al 34) reported that the rate of ankle injury can increase if the movements of the ankle joints decrease during drop-landing. The results of the present study correspond with these research results in that they present a statistically significant decrease in the right joint angle in the flatfoot group.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Tabrizi et al 34) reported that the rate of ankle injury can increase if the movements of the ankle joints decrease during drop-landing. The results of the present study correspond with these research results in that they present a statistically significant decrease in the right joint angle in the flatfoot group.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that a single application of a posterior talar glide does not have any acute effects on postural control and perhaps sensorimotor control in asymptomatic individuals. 6 However, McKeon and Hertel 32 suggested that differences in postural control among chronic ankle-instability patients may be partially a result of measurement sensitivity. Therefore, other methods of assessing postural control may elicit different findings.…”
Section: Discussionmentioning
confidence: 99%
“…6,36 Although the ankle complex moves in a triplanar motion, the mobilizations were performed in a single plane. Therefore, it is reasonable to believe that sway in the AP direction would be more affected than that in the ML direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations